COVID-19 Planning Among Radiologic Science Programs: Response Mitigation Activities. - Webster, Tammy L.; Clark, Kevin R. (Radiologic Technology)
Purpose To examine radiologic science programs' mitigation activities and educators' experiences related to coronavirus disease 2019 (COVID-19) response planning. Methods Using a mixed-methods approach, educators in magnetic resonance, medical dosimetry, radiation therapy, and radiography programs were surveyed to capture their experiences and mitigation strategies related to COVID-19 response planning. Quantitative data were summarized using descriptive statistics and percentages. Thematic analyses were performed on the qualitative responses. Results A total of 274 educators responded. Educators reported being somewhat comfortable with modifying clinical experiences (79, 28.8%), moderately comfortable with adjusting assessment procedures (112, 40.9%), and extremely comfortable with changing delivery of didactic content (115, 42%). Incidentally, 220 (80.3%) educators thought adjusting to a new course delivery approach (eg, face-to-face to online format) was the greatest challenge for faculty during the pandemic. Notably, half of the educators in this study questioned the quality of online (remote) learning. Specific to program policies, educators indicated that access restrictions to campus buildings (263, 96%) and removal of students from clinical sites (254, 92.7%) were implemented during the pandemic. Discussion Educators self-reported a moderate to strong comfort level with curricular modification. The area of modification that yielded the most uncertainty arose from alterations of clinical experiences. Thematic analyses revealed concerns related to personal protective equipment procurement and clinical sites prohibiting students from completing rotations. However, educators created innovative alternatives to enhance clinical education by providing simulations, case study analyses, and virtual tours of facilities during the pandemic. Securing educational technology resources, such as lockdown browser software, and working with institutional instructional designers might provide some resolution to educators' concerns regarding the quality of online (remote) learning. Conclusion Archiving radiologic science programs' COVID-19 response efforts is important. The compilation of mitigation strategies will inform and guide programs on contingency planning for future pandemic and emergent conditions.